CAUSAL NEXUS BETWEEN CURRENCY EXPOSURE AND STOCK RETURNS OF NON-FINANCIAL MNCS UNDER TWO FINANCIAL CRISES IN MALAYSIA - Wan Suhaimi, Wan Nurhanan; Anuar, Aiza Liyana (I-iECONS e-proceedings, 2023)
Malaysia practises high level economic openness which makes it an interesting avenue to study currency exposure. Based on this, this paper comparatively examines the relationship between currency exposure and stock returns among non-financial multinationals corporations in Malaysia by utilising the OLS and Granger causality tests. These tests were run using data from 207 non-financial Malaysian under two financial crises namely the Asian financial crisis (AFC) and global financial crisis (GFC) in 1997 and 2008, respectively. The distinct foundations of these crises are believed to induce varying levels of currency exposure and different nexus between currency exposure and stock returns of the selected multinationals. The firm-level OLS estimation found that higher number of firms’ stock returns were affected by currency exposure compared to the composition of significantly affected firm in Granger causality estimation (regardless of the causal directions). Still, the significant relationship and bilateral causality under both estimations were comparatively higher during the AFC. With this, the findings answer the elemental questions of the paper that dictate different market foundations during AFC and GFC, as well as providing evidences on the potential varying significant levels when bilateral causality is considered (Granger causality) compared to unidirectional relationship (OLS). The detailed analyses may guide future researcher to conduct the study of currency exposure by approaching different direction of causal relationship between currency exposure and stock re and market conditions.